2013
DOI: 10.1007/s10529-013-1339-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of methane by Methylomicrobium album and Methylocystis sp. in the presence of H2S and NH3

Abstract: Oxidation of methane by methanotrophs, Methylomicrobium album and Methylocystis sp., was measured at several initial concentrations of H2S and NH3 in the headspace of stoppered flasks, at the same initial concentration of methane as sole carbon and energy source: 15 % (v/v). No effect was observed at 0.01 % (v/v) H2S and 0.025 % (v/v) NH3 in gas phase but over 0.05 and 0.025 % (v/v), respectively, they inhibited the oxidation of methane. The effect of H2S was stronger in Methylocystis sp. and both microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
1
13
1
Order By: Relevance
“…Here, lower methanol production might be associated with increasing inhibitory gases H 2 S and NH 3 present in the raw biogas. The maximum methanol production from synthetic gas mixture of CH 4 and CO 2 (4:1) is about 6-fold higher than 0.71 mM previously reported for CH 4 and CO 2 trichosporium IMV 3011 did not produce methanol from pure CH 4 (30%) under similar conditions.…”
Section: Mixture Of Ch 4 and Cocontrasting
confidence: 50%
“…Here, lower methanol production might be associated with increasing inhibitory gases H 2 S and NH 3 present in the raw biogas. The maximum methanol production from synthetic gas mixture of CH 4 and CO 2 (4:1) is about 6-fold higher than 0.71 mM previously reported for CH 4 and CO 2 trichosporium IMV 3011 did not produce methanol from pure CH 4 (30%) under similar conditions.…”
Section: Mixture Of Ch 4 and Cocontrasting
confidence: 50%
“…This earlier study indicated that the decrease in pH from 4.72 to 3.8 was detrimental to these microorganisms, whereas a pH drop to 4.72 did not appear to suppress this group of methanotrophs. This finding is supported by other research (Cáceres et al, 2014), where higher H 2 S (0.05% v/v)concentrations suppressed the growth of Methylobacter and Methylocystis methanotrophs. However, the process of acidification will be slower in a typical New Zealand dairy effluent pond due to its lower organic content.…”
Section: Discussionsupporting
confidence: 88%
“…Lack of methanol accumulation during all growth experiments also suggested that MDH activity was not inhibited by the CO2 present in the biogas. Additionally, the H2S content of the biogas was less than 50 ppm, which was much lower 277 than the levels inhibitory to methanotrophs (>100 ppm) (Cáceres et al, 2014). Overall, biogas 278 from a commercial scale AD system is a suitable growth substrate for strain 14B.…”
Section: Comparison Of Growth On Different Methane Sourcesmentioning
confidence: 93%